The Influence of Transformational Leadership and Training on Employee Performance Through Job Satisfaction as an Intervening Variable at PT. XYZ in Yogyakarta - Fortuna, Salma Windy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study is entitled "Analysis of the Influence of Transformational Leadership and Training on Employee Performance Through Job Satisfaction as an Intervening Variable at PT.XYZ in Yogyakarta." The purpose of this study was to determine the mediating effect of job satisfaction in the relationship between transformational leadership and training on employee performance. This study uses quantitative methods and uses questionnaires for data collection. This study used a population of 193 employees. The sampling technique in this study used the census method for all sewing department employees, with a sample size of 193 employees. This study uses simple and multiple linear regression analysis methods, t-test, F-test, and path analysis. The results showed that transformational leadership had a positive and significant effect on employee performance, training had a positive and significant effect on employee performance, transformational leadership had a positive and significant effect on job satisfaction, training had a positive and significant effect on job satisfaction, job satisfaction had a positive and significant effect on employee performance, job satisfaction could mediate the relationship between transformational leadership and employee performance, and job satisfaction could mediate the relationship between training and employee performance.